Biomems: Thermal Effects Analysis Of DNA Cocktail Solution (DCS) In A Microfluidic Channel - Khor, Hee Huat (Universiti Sains Malaysia, 2005)
BioMEMS and microfluidics technology are two areas of MEMS based application, which has found a lot of new grounds in the fields of medicine and health sciences. In a related development Polymerase Chain Reaction (PCR) is one of the areas where microfluidics MEMS can be applied. There are possibly a lot of new benefits such as reducing consumption of DNA cocktail solution (DCS), improving reliability, reducing the time it takes to complete the PCR process, using less power etc. A simulation of thermal analysis on static DCS in a single microfluidic channel under different conditions that includes environment and parametric changes are presented in this thesis. The analysis software ANSYS allows the creation of a simplified simulation model and also the thermal analysis of the model under the required conditions. The analyses include variation of heat generated from heater, change of ambient temperature and convection and also reduction of the heater size. All of which are analyzed under a no-flow condition environment with specific temperature ranges where the denaturing process and DCS is considered to be working optimally. The results are able to achieve the objectives and also to concur some of the theory presented from the literature. Besides that some new conclusive information on thermal effects due to parametric changes are also presented in this thesis.